Pockenbank, Namibia - Schmidt, Isabell; Ossendorf, Götz; Bubenzer, Olaf; Henselowsky, Felix; Luyt, Julie; Sealy, Judith; Hensel, Elena (Handbook of Pleistocene archaeology of Africa, 2023)
Pockenbank rock shelter is located in south-western Namibia and contains a rich Late Pleistocene and Holocene sequence of Middle to Later Stone Age (MSA - LSA) human occupation (Marine Isotope Stage [MIS] 4 to MIS 1), including the rarely encountered Early LSA dated to MIS 2. The site’s newly dated and reinvestigated stratigraphy fits into a regional settlement history that is characterized by phases of alternating presence and absence of humans in rock shelters. In Namibia, a similarly extensive stratigraphic sequence is known only from the site Apollo 11, located 80 km to the south. The Pleistocene deposits at Pockenbank rock shelter have yielded a variety of organic and inorganic finds imported and/or modified by humans. These include lithic materials, animal bones and teeth, burned seeds and wood, ostrich eggshells, pigments, marine shells, and, maybe, although scarcely observed, land snails. The lithic assemblages are made from very fine-grained quartzite varieties, quartz and crypto-crystalline silica (CCS), with changing ratios as well as clearly changing technological, economic, and typological characteristics. The occupation intensity observed during the Late MSA and Early LSA, including the Last Glacial Maximum (LGM), is outstanding in the site’s wider context and might be linked to population dynamics related to changes of rainfall regimes during the LGM. Several issues at the site require further investigation. These include age determination of deposits older than 50 ka, the horizontal and vertical changes in preservation of organic material, and the documentation of sterile layers and hiatuses across larger areas.